Determination of relationship σ(ϵ) over the yield stress of concrete reinforcing steels/Tempiamosios armatūros σ(ϵ) priklausomybės virš takumo ribos nustatymas - Marčiukaitis, Gediminas; Šneideris, Arnoldas (Journal of Civil Engineering and Management, 1999)
Calculating and designing the tension zone of strengthening concrete structures and analysing its workability in stages which are close to break-up stage and distribution internal forces, existing various reinforcements, it is necessary to know characteristics of deformation and their change. Experiments show that forms of relationship between stress and strain of concrete reinforcing steels have great influence on accuracy of determination of reinforced concrete structures during all work stages of these structures. There are various analytic expressions for describing relationship of stress-strain and deformation of reinforcement. Our analysis showed that results of calculation for the same type of reinforcement are different. Methods suggested by Eurocode 2 also do not give accurate analytic expression of σ(ϵ) diagrams part over yield limit. The analysis and comparison of offered analytic σ(ϵ) expressions showed that the basis of a more accurate description of this relationship may be the accepted formula (16). Its application for description of σ(ϵ) relationship of different classes of reinforcing steel is suggested. Formula (17) is suggested for description of σ(ϵ) over yield point. Equation (19) is suggested for description of mild steels and deformation of reinforcement over yield limit by standard ISO–100 80. Article in Lithuanian. First Published Online: 26 Jul 2012